East-Central European human geographers in English-dominated, Anglophone-based international publishing space - Bajerski, Artur. Autor; Przygoński, Krzysztof. Autor (IGiPZ PAN, 2018)
A number of investigations have recently been devoted to the issues of inequalities in the international academic discourse. Hardly any of them concern, though, scholarly publishing practices and the actual utilization of the scientific output of non-Anglophone geographers, especially those from regions undergoing a neoliberal turn in the management of tertiary education and science. The following article aims to partly fill the gap through a close bibliometric analysis of the participation of researchers from East-Central Europe in international human geography. The investigation makes use of information about articles published in 48 geographical journals indexed in Web of Science. The results of the examination reveal that the share of researchers from East-Central Europe in the international geographical discourse is rather inconsiderable. The geographers struggle with the following problems: (1) publishing in a limited group of periodicals (concerning mostly the issues of Europe) coupled with a dearth of publications in important American and British societal journals as well as the ones of a more radical orientation; (2) infrequent citations of their works as compared to those of Anglophone and Western European researchers. All this is accounted for, inter alia, by (1) the negative impact the socialist period had on the development of social sciences, (2) a poor command of English, (3) a research focus on well-established and ‘safe’ themes as well as (4) the mechanisms of the Anglophone dominance in science. Giving all these handicaps careful consideration, the authors formulate the idea of doublepublication policy aimed at ameliorating the discussed problems.
24 cm
Keywords: East-Central Europe; geographers; bibliometric analysis; scientific communication; Anglophone domination; English language